2015
DOI: 10.3109/15376516.2015.1090512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on phenol content, antioxidant activity and biological activity of black maca and red maca extracts (Lepidium meyenii walp)

Abstract: This study was performed to determine the effects of gamma irradiation on UV spectrum on maca, total content of polyphenols, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activities and in vivo biological activities of red and black maca extracts (Lepidium meyenii). Adult mice of the strain Swiss aged 3 months and weighing 30-35 g in average were used to determine biological activities. Daily sperm production, effect on testosterone-induced prostate hyperplasia and forced swimming test were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…38 It has been reported that antioxidant capacity of alkaloids are more relevant than polyphenols metabolites in L. Meyenii, 39 and black maca presents a higher antioxidant activity than red maca. 40 Therefore, these findings suggest that treatment with maca extracts or estradiol replacement causes a recovery from the imbalance of oxidative stress in the menopausal model of OVX rats exposed to hyperbaric hypoxia.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…38 It has been reported that antioxidant capacity of alkaloids are more relevant than polyphenols metabolites in L. Meyenii, 39 and black maca presents a higher antioxidant activity than red maca. 40 Therefore, these findings suggest that treatment with maca extracts or estradiol replacement causes a recovery from the imbalance of oxidative stress in the menopausal model of OVX rats exposed to hyperbaric hypoxia.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, chemical composition of L meyeni shows polyphenols, glucosinolates, alkamides, and non‐starch polysaccharides which have potent antioxidant activity in vitro 36 can also increase the cellular antioxidant status of superoxide dismutase, glutathione peroxidase, and glutathione s‐transferase levels in hereditary hypertriglyceridemic rats, 37 or even in alcoholic mice 38 . It has been reported that antioxidant capacity of alkaloids are more relevant than polyphenols metabolites in L. Meyenii , 39 and black maca presents a higher antioxidant activity than red maca 40 . Therefore, these findings suggest that treatment with maca extracts or estradiol replacement causes a recovery from the imbalance of oxidative stress in the menopausal model of OVX rats exposed to hyperbaric hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, g-rays significantly increased the antioxidant activity of the polyphenols of the red and black maca extracts ( Lepidium meyenii walp ) and UV-C irradiation increase the total flavonoids and the reducing power of the fresh cut mango ( Mangifera indica L. cv. Chokanan) [ 17 , 18 ]. Therefore, our encouraging results may utilize to use UV-irradiation to enhance the extraction of the antioxidants as an assisted method of extraction using aqueous media.…”
Section: Discussionmentioning
confidence: 99%
“…Black maca has more total phenols than red and yellow maca. Despite black maca shows more antioxidant activity than red maca, the methanol extract of yellow maca presents more DPPH scavenging activity than that of black maca [6,7]. When compared to yellow, pink, violent and lead hypocotyls, total phenols are highest in yellow maca ( Table 1) [8].…”
Section: Phenolsmentioning
confidence: 98%